Influence of hormone therapy on the development of breast cancer in transgender women: A literature review (Research, Society and Development, 2024)
Objective: The present study aims to correlate hormonal therapy with the development of breast cancer in transsexual women, as well as describe the findings of hormonal therapy in transsexual women correlating with the possible development of breast cancer. Methods: Integrative Literature Review of a descriptive nature. For analysis of data on cases of breast cancer in transgender women and the possible influence of hormonal therapy. When 6 articles were selected, they were carefully analyzed in a qualitative and quantitative manner. Results: Transsexual women who are seeking a feminization process are at risk of developing breast cancer, due to increased levels of estrogen in the circulation. Therefore, the risk of developing breast malignancy in transgender women is 47 times greater than in cisgender men, however, this risk is reduced compared to cisgender women. Trans women have fewer mammograms than cisgender women. Conclusion: The relationship is still not clear when compared to cisgender women. There are reports that indicate a correlation between exposure above physiological levels of estrogen and breast cancer, but some authors defend the thesis that the trans population would not be exposed to hormones for a long enough period of time for the development of malignant neoplasia.